2022
DOI: 10.1136/bmjopen-2022-063902
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of self-reported lifetime medical diagnosis of depression in Brazil: analysis of data from the 2019 Brazilian National Health Survey

Abstract: ObjectivesTo assess the prevalence of and factors associated with the lifetime medical diagnosis of depression in Brazil.DesignPopulation-based, cross-sectional study.SettingAnalysis of data from the 2019 Brazilian National Health Survey.Participants90 846 individuals aged ≥15 years were included.Outcome measureThe self-reported medical diagnosis of depression at some point in one’s life was the main outcome. Prevalence ratios (PRs) with 95% CIs were calculated by Poisson regression with robust variance. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In Argentina, the poor economic situation in recent years may underly the higher level of anxiety in subjects with DGBI. In Brazil, in a nationwide population study, the lifetime‐self reported medical diagnosis of depression was almost 10%, and more frequent among women than men, which can explain the higher rates of depression among subjects with DGBI in that country 36 . In addition, a previous study among 113 consecutive patients with Rome III IBS showed that anxiety and/or depression using the Hospital Anxiety and Depression Scale (HAD) were found in 81.5% of the patients 37 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In Argentina, the poor economic situation in recent years may underly the higher level of anxiety in subjects with DGBI. In Brazil, in a nationwide population study, the lifetime‐self reported medical diagnosis of depression was almost 10%, and more frequent among women than men, which can explain the higher rates of depression among subjects with DGBI in that country 36 . In addition, a previous study among 113 consecutive patients with Rome III IBS showed that anxiety and/or depression using the Hospital Anxiety and Depression Scale (HAD) were found in 81.5% of the patients 37 .…”
Section: Discussionmentioning
confidence: 97%
“…In Brazil, in a nationwide population study, the lifetime-self reported medical diagnosis of depression was almost 10%, and more frequent among women than men, which can explain the higher rates of depression among subjects with DGBI in that country. 36 In addition, a previous study among 113 consecutive patients with Rome III IBS showed that anxiety and/or depression using the Hospital Anxiety and Depression Scale (HAD) were found in 81.5% of the patients. 37 Our findings among subjects with DGBI in Brazil was further impacted by the lower scores for mental health HRQOL among them, suggesting that patients with DGBI from Brazil and Argentina may require psychological support and providers need to be alert to symptoms and signs of anxiety and depression.…”
Section: Anxietymentioning
confidence: 99%
See 1 more Smart Citation